PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA DAN DISIPLIN KERJA SEBAGAI VARIABEL MEDIASI DI DINAS KESEHATAN KABUPATEN PASER - Arniah; Andi Setiawan (Journal Publicuho, 2024)
The aim of the research is to determine the influence of transformational leadership, discipline, motivation and work environment on employee performance at the Paser District Health Service. tUsing path analysis with the help of the PLS tsoftware program. The results of the analysis show that transformational leadership has a significant influence on the work motivation of employees at the Paser District Health Service. The work environment has a significant influence on the work discipline of employees at the Paser District Health Service. Work motivation has a significant influence on the performance of employees at the Paser District Health Service. Work discipline has a significant influence on the performance of employees at the Paser District Health Service. Transformational leadership has a significant effect on employee performance at the Paser District Health Service. The work environment has a significant influence on the performance of employees at the Paser District Health Service. Transformational leadership has a significant influence on employee performance at the Paser District Health Service with work motivation as mediation by television. The work environment has a significant influence on the performance of employees at the Paser District Health Service with work motivation as the mediating variable